"Language Is What Makes Everything Easier": The Awareness of Semiotic Resources of Mexican Transnational Students in Mexican Schools. Issue 1 (2nd January 2019) - Despagne, Colette
ABSTRACT: This study explores how transnational students who go or return to Mexico understand the complexities of language, identity and schooling in their new context after having been raised and educated in the United States. The study used narrative networks and Blommaert's discourse analysis framework to analyze the narratives of twenty transnational students to investigate their integration into schools and how they understood the process of becoming Mexicans in Mexico. The results highlight how their initial unfamiliarity with institutional expectations of normalcy resulted in their being silenced, socially excluded, and misunderstood. The findings illustrate how, over time, many students developed dexterity in reading local contexts and offered semiotic displays to be understood in the way they desired. This required flexibility in orienting to authoritative centers that differed between the United States and Mexico and understanding complex power structures within Mexico, in which there were limited opportunities to be positively identified as bilingual Mexicans.